Investigating the role Of CBX2 to promote cell growth in triple negative breast cancer - Bilton, Lucie (2022)
Breast cancer is the uncontrolled proliferation of breast cells and is one of the most common cancers in the UK. It is a complex disease that can be divided into different subtypes based upon the presence or lack of hormone receptors, namely the oestrogen receptor(ER), progesterone receptor (PR) and human epidermal factor receptor 2 (HER2). Breast cancer without hormone receptor expression is called basal-like or triple negative breast cancer (TNBC). TNBC is more aggressive, and patients tend to have a poor prognosis partly due to a lack of targeted treatment. The identification of new therapeutic options for TNBC is therefore needed. Dysregulated epigenetic control of the chromatin state, and therefore gene expression, via aberrant chemical modification of histone proteins can play an important role in cancer progression. Previous studies have shown that the epigenetic regulatory protein, CBX2, which modulates histone ubiquitination and repression of gene expression, is implicated in breast cancer development. The aim of this study was to investigate the role of CBX2 and its effect on cell growth in TNBC using the TNBC cell lines MDA-MB-231 and MDA-MB-468, to help determine whether CBX2 is a viable potential therapeutic target for TNBC. In this study we showed successful knockdown of CBX2 in both TNBC cell lines using small interfering RNAs (siRNAs). We showed that expression of the tumour suppressor proteinRBL2 was upregulated after CBX2 knockdown, suggesting CBX2 represses the expression of RBL2. RBL2 is a member of the DREAM complex which prevents progression through the cell cycle via inhibition of key cell cycle genes. Gene expression profiling showed that CBX2 knockdown increased RBL2expression and reduced the expression ofRBL2target genes(PLK1, AURKA, CCNA2, CDK1). Chromatin immunoprecipitation (ChIP) showed thatCBX2 knockdown increased enrichment of RBL2at DREAM complex target sites, therefore demonstrating that CBX2 plays a role in promoting cell growth and proliferation via repression of DREAM complex activity. This study adds insight into the mechanisms by which CBX2 promotes progression of TNBC and shows the potential of CBX2 as a new therapeutic target.
Keywords: Biomedical sciences